Evaluating methane adsorbed film densities on activated carbon in dynamic systems. (December 2018) - Prosniewski, Matthew; Gillespie, Andrew; Knight, Ernest; Rash, Tyler; Stalla, David; Romanos, Jimmy; Smith, Adam
Highlights: Adsorption in small and large pores operates on different time scales. Densities in small pores saturate quickly around 0.35 kg/L. Densities in large pores are highly dependent on the loading procedure. The adsorbed film volume changes with the system's temperature. Abstract: Dynamic methane loading and discharge experiments on a 40 L adsorbed natural gas tank containing 20.5 kg of monolithic carbon adsorbent have been combined with pore volume data from subcritical nitrogen isotherms to evaluate the density and dynamic properties associated with adsorbed methane. The time-dependent density of the adsorbed gas was evaluated for narrow and wide micropores. The temperature-dependent adsorbed film volume was determined from the Ono-Kondo model and compared with the total micropore volume. The resulting adsorbed methane density evolves in two distinct parts. The density increases rapidly during the beginning of the loading process and increases slowly after narrow pores reach saturation. The narrow pores' saturated adsorbed gas densities ranged from 0.26 – 0.35 kg/L, depending on the choice of film volume. The density of wide micropores was found to be highly dependent on the loading procedure due to the expected temperature dependence of the film volume. During discharge, it was found that the wide micropores deplete early while narrow micropores deplete slowly which causes the less than 100% efficient discharges seen in adsorbed natural gas systems. These density models have been applied to accurately predict the gravimetric excess adsorption of other carbon adsorbents at 35 bar and explain previously published pressure and temperature relations during tank loading.